Use of Infographics in Information Retrieval: Coronavirus Study - Ohmaye, Helio; Paletta, Francisco Carlos (Cadernos de Educação Tecnologia e Sociedade, 2022)
Because of the new coronavirus, we incorporate novel words and concepts into our daily lives, appropriated in linguistics. In the environment of the “new normal, flattening the curve, asymptomatic, comorbidity, community transmission, herd immunity, lockdown, quarantine, social distancing, live and home office,” among other terms, constitutes a glossary assimilated by society. Times of crisis are usually accompanied by a leap in intellectual and technological innovation, as we look back at the two world wars and the pandemics that occurred in the 20th century. The literature review from the bibliographical research in editorial databases, related to infographics’ area, especially in the context of the production of descriptive documents, reveals the non-existence of material. With the developments that occurred with the closing of cultural institutions, such as museum and library, daily news with the pandemic theme and social isolation, the option of quantitative research was directed to informational dissemination bodies and entities containing infographics. The bibliometric method conducted in a non-present and remote format presents results that justify the technical and theoretical treatment related to the effect caused by the coronavirus and/or COVID-19, without the objective of comparison.